Optimization of operating modes of power units of nuclear power plants - Yefimov, Olexander Vyacheslavovich; Kavertsev, Valery Leonidovich; Tiutiunyk, Larysa Ivanivna; Harkusha, Tetyana Anatoliivna; Motovilnik, Anastasiia Vadimovna; Sydorkin, Igor Dmytrovych (Національний технічний університет "Харківський політехнічний інститут", 2023)
The materials of the article consider the main methodological provisions of calculations and optimization of NPP power unit equipment parameters using mathematical modeling methods. For the effective implementation of tasks related to determining the optimal parameters and structures of NPP power unit equipment using mathematical modeling and well-developed multifactor optimization methods, it is necessary to fulfill a number of requirements at their productions. Practice shows that it is impractical to optimize with the help of a single mathematical (simulation) model the entire set of parameters characterizing a given power unit, because with such a formulation, the optimization tasks are often mutually incorrect due to a significant discrepancy in the accuracy of various source information, unequal influence of parameters on the target function, specific differences in the mathematical description of various units and elements of the power unit. In order to effectively optimize the parameters of NPP power units, it is necessary to create a system of interconnected mathematical models, which include: a group of detailed mathematical models of individual units and elements of power unit equipment; more generalized mathematical models for the main equipment of power units built on their basis; complete mathematical model of power units.

У матеріалах статті розглянуті Основні методичні положення розрахунків та оптимізації параметрів устаткування енергоблоків АЕС методами математичного моделювання Для ефективної реалізації задач, пов'язаних з визначенням оптимальних параметрів і конструкцій устаткування енергоблоків АЕС за допомогою математичного моделювання й добре розроблених методів багатофакторної оптимізації, необхідно виконання ряду вимог при їх постановці. Практика показує, що недоцільно оптимізувати за допомогою однієї математичної (імітаційної) моделі весь комплекс параметрів, що характеризують даний енергоблок, оскільки за такої постановки задачі оптимізації часто бувають взаємно некоректні внаслідок значної невідповідності в точності різної вихідної інформації, нерівнозначності впливу параметрів на цільову функцію, специфічних відмінностей математичного опису різних вузлів і елементів енергоблоку. Для ефективної оптимізації параметрів енергоблоків АЕС необхідно створення системи взаємопов'язаних математичних моделей, що включають до себе: групу докладних математичних моделей окремих вузлів і елементів устаткування енергоблоків; побудовані на їх основі більш узагальнені математичні моделі для основного устаткування енергоблоків; повну математичну модель енергоблоків.
Оптимізація режимів роботи енергоблоків атомних електростанцій
Keywords: installation of NPP power units; methods of mathematical modeling; устаткування енергоблоків АЕС; методи математичного моделювання